Resistensi Muhammadiyah dan Nahdlatul Ulama terhadap Gerakan Salafi-Wahabi - Fathony, Bimba Valid (Canonia Religia, 2025)
The massively growing Salafi-Wahabi movement in Indonesia has received rejection from various elements of society, including within Muhammadiyah and traditionalist groups such as Nahdlatul Ulama (NU). Salafi-Wahabi is considered to bring a different understanding of Islam and is often not in line with local culture and Indonesian values. In the context of Muhammadiyah, resistance arose because of the infiltration of Salafi-Wahabi ideology, which was considered to weaken the decisions and direction of the Muhammadiyah movement itself. Ideological differences and approaches to preaching are the primary sources of tension between the two. Meanwhile, NU firmly rejects the purification ideology adopted by Salafi-Wahabi, because it is considered to damage the diversity of religious traditions in society. Salafi-Wahabi preaching, which tends to blame the practices of NU members, also strengthens the organisation's rejection of them. This study uses a qualitative method, namely library research. The results of the survey show that Salafi-Wahabi, as a transnational Islamic movement, needs to be watched out for because it often does not follow the moderate and tolerant character of Nusantara Islam. Resistance from Muhammadiyah and NU is a form of defence against Islamic values ​​that are contextual and rooted in local culture.